1984
DOI: 10.1016/0092-8674(84)90324-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer-like properties of the 60/81 bp elements in the ribosomal gene spacer of Xenopus laevis

Abstract: The spacer region of the Xenopus laevis ribosomal gene contains blocks of repetitive sequence elements that are 60 or 81 bp long. These 60/81 bp elements function as enhancer elements for the RNA polymerase I promoter at the 5' end of the gene. An RNA polymerase I promoter adjacent to a block of 60/81 bp elements is always dominant over a promoter on a second plasmid when both are coinjected into oocyte nuclei. If two promoters are placed on the same plasmid containing enhancers, both promoters come under thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
191
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 208 publications
(198 citation statements)
references
References 23 publications
7
191
0
Order By: Relevance
“…In addition, we have reported that sequences in the intergenic spacer region of the Xenopus laevis ribosomal genes have enhancer-like activity on the RNA polymerase I promoter that directs transcription of the 7.5 kilobase rRNA precursor (4). The observation that promoters for RNA polymerase I as well as for RNA polymerase II utilize enhancers strengthens the idea that enhancers perform a vital function that may turn out to be required by all eukaryotic promoters.…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations
“…In addition, we have reported that sequences in the intergenic spacer region of the Xenopus laevis ribosomal genes have enhancer-like activity on the RNA polymerase I promoter that directs transcription of the 7.5 kilobase rRNA precursor (4). The observation that promoters for RNA polymerase I as well as for RNA polymerase II utilize enhancers strengthens the idea that enhancers perform a vital function that may turn out to be required by all eukaryotic promoters.…”
Section: Introductionsupporting
confidence: 49%
“…Most of our experiments have been done with a block of ten of these 60/81bp repeats which we employ as an enhancer cassette. '40, * 52, pXlr4Ol, and pXlr521 have been described previously (4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Blocks of 60/81-bp repeats in the intergenic spacer of Xenopus ribosomal genes function as transcriptional enhancers (Labhart and Reeder 1984) and are among the best characterized UBF-binding sites. UBF binds cooperatively to these Xenopus Enhancer (XEn) elements Putnam and Pikaard 1992) and is required for enhancer function (McStay et al 1997).…”
Section: Generation and Mapping Of Heterologous Ubf-binding Site Arraysmentioning
confidence: 99%